Pengaruh Citra Merek, Kualitas Produk Dan Persepsi Hargaterhadap Minat Beli Konsumen Deterjen Attack: Studi Kasus Pada Ibu Rumah Tangga di Kota Bogor - Septiani, Murti; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Marketing in modern times is no longer focused on how the product sells, but there are many factors and strategies that companies must have. The development of the detergent industry in Indonesia is growing very rapidly. Evidenced by the number of circulating various brands. Detergent is one of the industrial products that is very important in everyday life, especially for household and industrial purposes. Detergents can be in the form of liquid, paste, or powder containing constituents of the active ingredients on the surface and constituents of additives. The purposes of this study are (1) to determine and analyze the effect of brand image on consumer buying interest, (2) to determine and analyze the effect of product quality on consumer buying interest, (3) to determine and analyze the effect of price perception on consumer buying interest ( 4) To find out and analyze the effect of Brand Image, Product Quality and Price Perception together on Consumer Buying Interest. The number of respondents in this study found 100 respondents who were taken from housewives in the city of Bogor. The research data was processed using SPSS. The results of this study are as follows: (1) Brand Image has a positive and significant effect on Buying Interest in Attack detergent products with a regression coefficient value of 0.340 and a significant value of 0.028. (2) Product quality has a positive and significant effect on Buying Interest in Attack detergent products with a regression coefficient value of 0.272 and a significant value of 0.029. (3) Price Perception has a positive and significant effect on Buying Interest on Attack detergent products with a regression coefficient value of 0.325 and a significant value of 0.012. (4) Brand Image, Product Quality and Price Perception together have a positive and significant effect on Purchase Interest in Attack detergent products with a calculated F value of 28.912 and greater than the F table of 2.70 and has a significance value of 0.000. Keywords: Brand Image, Product Quality, Price Perception and Consumer Buying Interest